Frequency of Postoperative Ileus after Exploratory Laparotomy in Patients Admitted at Tertiary Care Hospital - Ghansham, Najeeb Ullah, Saba Patoli, Vijay Kumar, Bilal Burki, Mehwish Ali, Mahwash Mansoor, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: To determine the frequency of postoperative ileus after exploratory laparotomy in patients admitted at Tertiary Care Hospital, Karachi. Study Design: Descriptive cross-sectional study. Place and Duration of Study: Study was conducted at Department of Surgery, Jinnah Postgraduate Medical Center (JPMC), Karachi, from June 2018 to June 2021. Methods: Data was prospectively collected from patients after taking a verbal consent. 165 patients who met the diagnostic criteria were included. Quantitative data was presented as simple descriptive statistics giving mean and standard deviation and qualitative variables was presented as frequency and percentages. Effect modifiers were controlled through stratification to see the effect of these on the outcome variable. Post stratification chi square test was applied taking p-value of ≤0.05 as significant Results: A total of 165 patients underwent exploratory laparotomy were included in this study. Mean age, duration of surgery, duration of symptoms, height and weight in our study was 44.21±7.24 years, 2.12±1.65 hours, 10.35±3.21 hours, 148.11±18.47 cm and 58.21±11.25 respectively. 76 (46.1%) were male and 89 (53.9%) were female. Out of 165 patients, 42 (25.5%) and 123 (74.5%) had and did not have postoperative ileus. Conclusion: Postoperative ileus occurs commonly after abdominal operations and is one of the limiting factors preventing early hospital discharge. Enhanced recovery programs, grouping together all measures for prevention or cure of POI by addressing the mechanisms of POI can reduce the duration of hospitalization, morbidity and interval to resumption of transit. Keywords: Postoperative ileus, surgery, mortality, morbidity and exploratory.